Eksistensi dan Peran Musyrif dalam Pembentukan Kepribadian Islami Siswa - Hadi, Muhammad Wafi Hilman Luthfil; Ali, Mohamad (Hikmah, 2023)
This research aims to explore the role of musyrif in forming the Muslim personality of students at SMA IT Nur Hidayah Sukoharjo along with the supporting and inhibiting factors in forming the student’s Muslim personality. This research is qualitative research using a phenomenological approach. The data sources are the deputy head of the school for homelessness, musyrif, and class XII homestead students. Data  analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that the role of the musyrif in forming the Muslim personality of the students at SMA IT Nur Hidayah Sukoharjo is, namely, 1) being a facilitator, 2) accustoming students to the discipline of worship, 3) supervising and accompanying students’ worship activities, 4) giving rewards and punishments, 5) providing advice and motivation, 6) organizing sports activities, 7) being a role model for students, 8) being a second parent. The supporting factors for the success of musyrif in forming Muslim personalities at home for students at SMA IT Nur Hidayah Sukoharjo are, namely, 1) facilites and infrastructure, 2) established regulations, 3) conducive environment, 4) good musyrif competence. The inhibiting factors are, namely, 1) students’ educational background, 2) students’ character, 3) number of musyrif.